Differential Mechanisms of Action and Efficacy of Vitamin E Components in Antioxidant Cytoprotection of Human Retinal Pigment Epithelium - Duncan, R. Scott; Hurtado, Daniel T.; Hall, Conner W.; Koulen, Peter (Frontiers in Pharmacology, 2022)
The purpose of this study was to determine if different vitamin E components exhibit similar efficacy and mechanism of action in protecting retinal pigment epithelial (RPE) cells from oxidative damage. We hypothesized that α-tocopherol (αT) is unique among vitamin E components in its cytoprotective mechanism of action against oxidative stress in RPE cells and that it requires protein synthesis for optimal antioxidant effect. We used cell viability assays, fluorescent chemical labeling of DNA and actin and immuno-labeling of the antioxidant proteins Nrf2 and Sod2 and of the tight junction protein, ZO-1, and confocal microscopy to determine the effects of αT and γT against oxidative stress in immortalized human RPE cells (hTERT-RPE). Using the four main vitamin E components, αT, γT, δ-tocopherol (δT) and α-tocotrienol (αTr), we ascertained that they exhibit similar, but not identical, antioxidant activity as αT when used at equimolar concentrations. In addition, we determined that the exposure time of RPE cells to α-tocopherol is critical for its ability to protect against oxidative damage. Lastly, we determined that αT, but not γT, partially requires the synthesis of new proteins within a 24-hour period and prior to exposure to tBHP for optimal cytoprotection. We conclude that, unlike γT and δT, αT appears to be unique in its requirement for transport and/or signaling for it to be an effective antioxidant. As a result, more focus should be paid to which vitamin E components are used for antioxidant interventions.